Kedudukan PT. Angkasa Pura I Dalam Pembayaran Bea Perolehan Hak Atas Tanah Dan Bangunan - HR, Ridwan; Harahap, Nurmalita Ayuningtyas; Mardhatillah, Siti Ruhama (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This paper examines the issues of, first, the special assignment of the Minister of BUMN (State Owned Enterprise) and the Minister of Transportation to PT. Angkasa Pura I (Persero) in land procurement forthe construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, DIY Province whether it can invalidate the obligations of PT. Angkasa Pura I (Persero) to pay BPHTB. Second, it is regarding the land procurement for the construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, Special District of Yogyakarta whether it can be qualified as "land acquisition for the development of public interest" which is freed from the obligation to payBPHTB. This is a normative legal research using primary and secondary legal materials obtained through literature studies and is analyzed juridical. From the research results, it can be concluded that, first, special assignments could not invalidate the obligations of PT. Angkasa Pura I (Persero) to payBPHTB. Secondly, PT. Angkasa Pura I (Persero) in Kulon Progo Regency of Special District of Yogyakarta Province cannot be qualified as "land acquisition for development for public interest" freed from the obligation to pay BPHTB.